Petit récit de l’émergence de la recherche-création médiatique à l’UQAM et quelques propositions pour en guider la pratique - Louis-Claude Paquin; Cynthia Noury (Communiquer)
What could be the specificities of mediatic research-creation practiced in the field of communications? In an attempt to provide a preliminary answer to this question, our small narrative takes as a context the development of graduate programs in research-creation at Université du Québec à Montréal’s (UQAM) Faculty of Communication since the 1980s. We will first pose research-creation as a diverse set of practices aimed at producing various types of knowledge by linking these two components, then we will present a series of distinctions between the aims of artistic and creative media practices. This reflective journey allows us to identify several proposals to guide this set of practices in the context of communication studies, as well as to highlight some of UQAM’s contributions in fostering research-creation.